Management strategy for halal tourism development in Blitar - Farizan, Fahmi Ahmad; Hartini, Sri (Journal of Halal Product and Research (JHPR), 2025)
Halal tourism has become the main focus for many tourism destinations around the world, including Blitar, Indonesia. Blitar has enormous tourism potential with its natural, historical and cultural riches. The aim of this research is to formulate effective strategies needed to develop Blitar as a halal tourism destination. The research method used is a qualitative descriptive approach to understand the halal tourism development strategy in Blitar. Data was obtained through literature study and direct observation of research objects. The results of this research are that Blitar has a lot of potential to be developed into a halal tourism destination. Starting from a wealth of natural tourism, artificial tourism, religious tourism, culinary tourism, to cultural history tourism which is a special attraction for tourists. The development of halal tourism in Blitar can be seen through several aspects including tourist objects and destinations, provision of infrastructure and accessibility, as well as human resource development. The potential for halal tourism development is analyzed through the strategic approaches SO (strengths-opportunities), WO (weaknesses-opportunities), ST (strengths-threats), and WT (weaknesses-threats). Appropriate strategic management is the key to success in developing halal tourism in Blitar.   Keywords: Management, Strategy, Halal Tourism, Blitar